Technologies of virtual reality and perspectives of their application in mortgage lending - E. I. Shamanina; S. A. Larina; S. A. Tadevosyan (E-Management)
The article discusses issues related to the development trends of the Russian mortgage lending market, reveals the essence and substantiates the relevance of the introduction of virtual technologies in the process of providing mortgage loans. The main purpose of the study is to analyze current trends in the Russian mortgage lending market, identify existing problems in the process of providing mortgage loans, and develop proposals for further development and improvement of this type of lending. Particular attention during the study was paid to the peculiarities of the use of virtual technologies in the banking business. The implementation of the research goal is due to the solution of the following tasks: the current state and current trends in the Russian mortgage lending market are analyzed; shortcomings of client banking services in the organization of mortgage lending are indicated; analyzed the features of the use of virtual technologies in mortgage lending and the practice of individual Russian banks using virtual reality technologies when applying for a mortgage; the key business indicators of banks that have implemented virtual technologies are given, and the impact of the increase in the share of mortgage lending on the efficiency of their activities is analyzed. To accomplish these tasks in the course of the study, methods of scientific knowledge were used: logical, analytical, the method of comparative analysis, statistical methods of information processing. As the study showed, at present, mortgages are a key driver of growth in retail bank lending, being a reliable, high-quality and profitable asset in the loan portfolios of Russian banks, and the mortgage lending market itself is promising, dynamic, but still not sufficiently technologically advanced. The use of virtual technologies by banks will improve the quality of customer service, will contribute to the growth of mortgage lending and the further development of technological innovations in the banking sector.